Sol-gel insulation coatings on Monel/Fe/MgB2 wires for coil development - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
In this study, preparation, structure, morphology and thermal properties of ceramic insulation coating on Monel/Fe/MgB2 wires, which were fabricated by Hyper Tech Research Inc., using Continuous Tube Forming and Filling (CTFF) process were studied for coil development. Ceramic insulation coatings were prepared by reel-to-reel sol-gel method using solutions of Y and Zr based organometallic compounds. The coating thickness was controlled by number of coating, withdrawal speed and solution chemistry. 29 meter of Monel/Fe/MgB2 wire was insulated by Y2O3-ZrO2 using sol-gel method. Monel/Fe/MgB2 coil was layer wounded and impregnated with stycast. Sister samples of coil were tested between 4.2 K and 30 K with a Variable Temperature Insert (VTI) in a 20 T superconducting magnet using the analog DC pulse four-wire method with 1 (mu V/cm) criterion. The sample had a J(c) of 0.16 x 10(5) (A/cm(2)) at 4 T at 21 K. The surface morphologies and microstructure of sister samples of coil were characterized by ESEM, EDS, DTA, TGA and XRD. Resistance was measured by using HP 4339A High Resistance Meter.
Keywords: insulation; MgB2 coil; sol-gel; Y2O3-ZrO2; CRITICAL-CURRENT DENSITY; FIELD-DEPENDENCE; MGB2; FABRICATION; TRANSPORT; MAGNETS